Forever my girl [videorecording (DVD)] - Wolf, Bethany Ashton; Roe, Alex, 1990-; Rothe, Jessica; Fortson, Abby Ryder, 2008-; Tritt, Travis; McLaughlin, Heidi (Romance fiction writer) (Lionsgate, 2018)
After being gone for a decade, a country star returns home to the love he left behind.